Diagnostic and surgical management of the first reported case of bilateral schwannomas of seminal vesicle at a single center - Ma, Tao; Cao, Guihua; Du, Jianping; Wang, Lingfei; Wang, Jie (Frontiers in Surgery, 2025)
BackgroundSchwannomas are benign tumors originating from Schwann cells and are rarely found in the seminal vesicles. Due to their deep pelvic location and nonspecific symptoms, these tumors are often discovered incidentally during imaging or physical examinations. We report a rare case of bilateral schwannomas of seminal vesicle in an asymptomatic 68-year-old male, highlighting the diagnostic and treatment of such uncommon tumors.Case presentationThis case describes the successful diagnosis and management of bilateral schwannomas of seminal vesicle in an asymptomatic elderly male. Laparoscopic resection achieved complete tumor removal with no perioperative complications. Short-term follow-up showed favorable recovery and no evidence of recurrence.ConclusionSchwannomas of seminal vesicle is a rare, slow-growing disease with an insidious onset and low incidence, most commonly affecting middle-aged and elderly men. More than 40% of patients are asymptomatic. The tumor occurs with approximately equal frequency on either side, while bilateral involvement is exceedingly rare. Lesions are predominantly solid, and minimally invasive surgery—either laparoscopic or robotic—is the preferred treatment approach. The overall prognosis is favorable, and to date, no cases of recurrence or malignant transformation have been reported.